Spatial–Temporal Oxygenation Mapping Using a Near-Infrared Optical Scanner: Towards Peripheral Vascular Imaging - Leiva, Kevin; Leizaola, Daniela; Gonzalez, Isabella; Dargam, Valentina; Alirezaei, Haniyeh; Kaile, Kacie; Robledo, Edwin; Hutcheson, Joshua; Godavarty, Anuradha (Annals of biomedical engineering, 2023)
Near-infrared spectroscopy (NIRS)—based peripheral perfusion, or microcirculation, can be used to assess the severity of peripheral vascular dysfunction. A low-cost, portable non-contact near-infrared optical scanner (NIROS) was developed for spatio-temporal mapping of tissue oxygenation and perfusion in tissues. In vivo validation studies were carried out on control subjects ( n = 3) to assess the ability of NIROS to measure real-time oxygenation changes in response to an occlusion paradigm on the dorsum of the hand. NIROS captured real-time tissue oxygenation changes with 95% correlation when compared to a commercial device. A feasibility peripheral imaging study was performed in a mouse model ( n = 5) of chronic kidney disease (CKD) induced vascular calcification to assess differences in microcirculatory peripheral tissue oxygenation. The tissue oxygenation (in terms of oxy-, deoxy-, and total hemoglobin changes) due to the occlusion paradigm was distinctly different prior to (week-6) and after the onset of vascular calcification (week-12) in the murine tails. Future work will involve extensive studies to correlate these microcirculatory tissue oxygenation changes in the peripheral tail to the vascular calcification in the heart.